ISLAMISASI ILMU SEBAGAI IDENTITAS KEAGAMAAN (TELAAH KRITIS SYED NAQUIB AL-ATTAS) - Fahrudin Fahrudin; Henki Desri Mulyadi; Ahmad Shofiyuddin Ichsan (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2020)
This study aims to determine the Islamization of the science of Syed Naquib Al-Attas as a process of human liberation from magical, mythological, animistic, national-cultural traditions, and control of reason and language. The authors use the descriptive-analytic methods for library data that is relevant to the object of research. The results of this study indicate that the Islamization of the Syed Naquib Al-Attas science is an academic response in order to criticize the development of modern Western science which is considered to have fundamentally damaged the order of life. Al-Attas criticized the Western world view which had deified rational-empirical so that it is assumed that things that are supernatural and not visible to the human senses are something that cannot be trusted.